Tuber HCN and leaf phenols of 16 brazilian cassava (Manihot esculenta Crantz) cultivars as related to their resistance to bacterial blight - TELES, F. F. FEITOSA; Brune, Walter; Maia, Geraldo A.; Borges, Valéria E L.; Albuquerque, Tâmia T.; Fuckuda, Chigery; Romeiro, Reginaldo S. (Revista Ceres, 2015)
-